What happens >10 years after percutaneous septal ablation for hypertrophic obstructive cardiomyopathy? Ultra long-term follow-up of 120 patients. (25th November 2020) - Faber, L; Scholtz, S; Batzner, A; Seggewiss, H
Abstract: Introduction and methods: Recent registry analyses including the European multicenter registry (Euro-ASA) documented a favourable long-term outcome of septal ablation (ASA/PTSMA) competitive to surgical myectomy. There is no information about the period beyond 10 years. We therefore analyzed the outcome in 120 HOCM patients (pts., mean age @ index intervention: 62±13 years) treated with ASA who survived >10 years. Results: Mean CK rise during the index intervention was 537±258 U/l (reference: <80). A DDD-pacemaker (DDD-PM) had to be implanted in 26 pts. (22%) for procedure-related AV conduction problems. A re-intervention for residual or recurrent outflow obstruction (LVOTO) had to be performed in 12 pts. (10%; re-PTSMA: 10 pts.; myectomy: 2 pts). These cases included, at their last follow-up visit 107 pts. (89%) were in functional class I or II. During follow-up (159±33 [range: 122–264] months), 12 pts. (8%) died, of these 6 (4%) from non-cardiac, and 6 (4%) from cardiovascular causes including one sudden death. Furthermore, 4 (3%) ICDs were implanted (1 for secondary, 3 for primary prevention of sudden cardiac death). The most frequent clinical problem was atrial fibrillation which occurred in 27 pts. (23%), and which was refractory to rhythm control attempts in 21 pts. (18%). Conclusions: The procedure-related DDD-PM rate in this septal ablation cohort including the early learning curve more than doubled the current one. Nevertheless, during ultra long-term follow up a durable clinical improvement was observed with mortality rates around 1%/year, nearly equivalent to that of 0.8% observed in normal populations. Atrial fibrillation is a frequent problem in this elderly, formerly obstructive HCM population. Funding Acknowledgement: Type of funding source: None